2013
DOI: 10.1093/jpepsy/jss176
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Camp Attendance and Self-Perceptions in Children With Chronic Health Conditions: A Meta-Analysis

Abstract: Camp attendance is associated with small improvements in self-perceptions for children with some chronic health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…While promising, this literature on the impact of camp is relatively small, most were completed prior to current intensive insulin management protocols, [3][4][5] and the studies contain methodologic concerns, including relatively small sample size, 4,5,7 large ageranges, [2][3][4] and parent-only reports, 7 rendering it difficult to make conclusions about the impact of camp on diabetes outcomes. This study seeks to remedy these concerns by surveying campers and their parents from over 42 diabetes-specific summer programs from across the country, and assessing children separately from adolescents to assess respondent's perceptions regarding the potential benefits of attending camp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While promising, this literature on the impact of camp is relatively small, most were completed prior to current intensive insulin management protocols, [3][4][5] and the studies contain methodologic concerns, including relatively small sample size, 4,5,7 large ageranges, [2][3][4] and parent-only reports, 7 rendering it difficult to make conclusions about the impact of camp on diabetes outcomes. This study seeks to remedy these concerns by surveying campers and their parents from over 42 diabetes-specific summer programs from across the country, and assessing children separately from adolescents to assess respondent's perceptions regarding the potential benefits of attending camp.…”
Section: Introductionmentioning
confidence: 99%
“…While camp may offer a variety of psychosocial and self‐care behavior benefits, the literature assessing the impact of camp is relatively sparse. One meta‐analysis on the impact of camp on youth between 5 and 20 years of age, with a variety of chronic illnesses showed small, but statistically significant improvements in youth's self‐perceptions, but the studies of youth with diabetes were relatively old, with 1 from the 1970's, 2 each from the 1980s and 1990s, and 1 from the 2000's. Another study assessing the impact of camp with 90 youth between 6 and 16 years of age with a variety of chronic illnesses (32 with diabetes) found that children's attitudes toward their illness became significantly more positive after attending camp.…”
Section: Introductionmentioning
confidence: 99%
“…Medical camps are unique in their ability to tailor programming to the distinct medical and psychosocial needs of each pediatric condition. Indeed, there are many summer camp programs specific to a variety of chronic health conditions, such as kidney disease, cancer, sickle cell disease, HIV/AIDS, diabetes, obesity, and asthma . Campers are provided with ample opportunities to practice condition‐specific self‐management behaviors among knowledgeable medical staff and without assistance from their caregivers .…”
mentioning
confidence: 99%
“…[10][11][12] Campers are provided with ample opportunities to practice conditionspecific self-management behaviors among knowledgeable medical staff and without assistance from their caregivers. 10,11 Furthermore, given these young people commonly experience social isolation and low peer acceptance in school and other settings, the accepting, engaging atmosphere of camp may provide important and needed exposure for campers to practice social skills, build friendships, and strengthen social development. Indeed, meta-analytic research has found that young people who attend medical camp programs show improvements in important social outcomes, including self-perception and self-esteem.…”
mentioning
confidence: 99%
See 1 more Smart Citation